Odpowiedzi

Najlepsza Odpowiedź!
2010-02-23T20:09:45+01:00
A) 6(x-4)-2=6x-24-2=6x-26
b)2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)1/2(4x-4)-2x=2x-2-2x=-2
g)x(x-1)-3(x²-x)=x²-x-3x²+3x=-2x²+2x
h)5a(a-3)-3a(a-5)=5a²-15a-3a²+15a=2a²
i)3x(x+1/3y)-2y(1/2x-1/2)= 3x²+xy-xy+y=3x²+y
2010-02-23T20:13:40+01:00
A) 6(x-4)-2=6x-24-2=6x-26
b)2(x+1)-3(x-1)=2x+2-3x+3=-x+5
c)-3(y-2)+4(y+2)=-3y+6+4y+8=y+14
d)5(x-y-1)-4(x+2)=5x-5y-5-4x-8=x-5y-13
e)2(3a+b)-2(a-b)=6a+2b-2a+2b=4a+4b
f)1/2(4x-4)-2x=2x-2-2x=-2
g)x(x-1)-3(x[do kwadratu]-x)=x kwadrat-x-3x kwadrat-x=-2x-4x kwadrat
h)5a(a-3)-3a(a-5)=5a kwadrat-15a-3a kwadrat +15a=2a kwadrat
i)3x(x+1/3y)-2y(1/2x-1/2)=3x kwadrat+xy-xy+y=3x kwadrat +y